Korelacja wychowania religijnego i patriotycznego w koncepcji pedagogicznej błogosławionego Edmunda Bojanowskiego - Belina, Damian (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Blessed Edmund Bojanowski is the author of an original pedagogical concept designed to educate pre-school children. He saw in the young generation the hopes on revival of the family and the polish nation. Therefore Bojanowski recognized religion and patriotism as the basis of his pedagogical work. These two elements of education should be inherent and subjects of continuous correlation as these are the roots from which the Polish nation grows. Although the pedagogical concept of blessed Edmund Bojanowski was worked out in the 19th century still has not gone out of date. It is currently used in children’s educational work on different continents by the congregation of the Sisters Servants of the Immaculate Conception of the Virgin Mother of God. In this paper, the author focused on showing the correlation between religious and patriotic education contained in the pedagogical concept of blessed Edmund Bojanowski.